Type VI secretion system mutations reduced competitive fitness of classical Vibrio cholerae biotype - Benjamin Kostiuk (Nature Portfolio, 2021)
The bacterium Vibrio cholerae has caused seven recorded cholera pandemics. The factors responsible for the decline of 6th pandemic classical biotype strains are not well understood. Here, Kostiuk et al. propose that classical strains underwent sequential mutations in type-six secretion system genes that disadvantaged them when confronted with 7th pandemic El Tor biotype strains.